158k views
4 votes
Evaluate the integral
x4 – 2x2 + 4x + 1
x3 – x2 - x + 1
dx

1 Answer

3 votes

Looks like the integral is


\displaystyle\int(x^4-2x^2+4x+1)/(x^3-x^2-x+1)\,\mathrm dx

First simplify the integrand by long division (or however you like):


(x^4-2x^2+4x+1)/(x^3-x^2-x+1)=x+1+(4x)/(x^3-x^2-x+1)

Also notice that


x^3-x^2-x+1=x^2(x-1)-(x-1)=(x^2-1)(x-1)=(x+1)(x-1)^2

Split the last term into partial fractions:


(4x)/((x+1)(x-1)^2)=\frac a{x+1}+\frac b{x-1}+\frac c{(x-1)^2}


4x=a(x-1)^2+b(x+1)(x-1)+c(x+1)


4x=(a+b)x^2+(c-2a)x+a-b+c


\implies\begin{cases}a+b=0\\c-2a=4\\a-b+c=0\end{cases}\implies a=-1,b=1,c=2

So the integral is equivalent to


\displaystyle\int\left(x+1-\frac1{x+1}+\frac1{x-1}+\frac2{(x-1)^2}\right)\,\mathrm dx


=\displaystyle\frac{x^2}2+x-\ln|x+1|-\ln|x-1|-\frac2{x-1}+C


=\displaystyle\frac{x^2}2+x-\ln|x^2-1|-\frac2{x-1}+C

User Heinz
by
5.1k points